Exploration of Wien Displacement Law: A Fundamental Concept in Quantum Physics - Yohakim, Yoman Ribeta Ratu; Maodjud, Siti Hamia; Ngaga, Elisabeth Jaa; Jufriansah, Adi; Sahlan (Bincang Sains dan Teknologi, 2024)
This study explores the relationship between the temperature of a black body and the wavelength of the radiation it emits based on the Wien Displacement Law. This experiment collected maximum temperature and wavelength data using PhET simulation software and other supporting devices. The Wien Displacement Law states that the wavelength at which the maximum intensity of blackbody radiation occurs (λmax) is inversely proportional to the absolute temperature of the object (T). To test this law, the temperature of the blackbody was set at various values in the simulation, and the resulting maximum wavelength was recorded. The linear regression method analyzed the data to determine the temperature and maximum wavelength relationship. The analysis results showed a linear relationship with a coefficient of determination R2 = 1, indicating that the model fits the observed data well. The value of Wien's constant (b) calculated from the slope of the regression line is close to the theoretical value of 2.897 × 10-3 m.K, supporting the validity of the Wien Displacement Law. In conclusion, this study confirms that the maximum wavelength of electromagnetic radiation is inversely proportional to the absolute temperature of a blackbody, which agrees with the prediction of the Wien Displacement Law.